2021
DOI: 10.5055/jem.0597
|View full text |Cite
|
Sign up to set email alerts
|

Social media for emergency messaging with youth and families during the coronavirus 2019 (COVID-19) pandemic: Getting it right

Abstract: Disaster communications are frequently included as an area of improvement in the majority of incident after action reports. One segment of the population that is overlooked or intentionally excluded from messaging constructs is adolescents and transitional aged youth. Social media, the preferred mechanism of this population, has the capacity to both educate as well as misinform. Thoughtful and intentional utilization of social media channels for adolescent audiences can convey facts and motivation for appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…going viral for the wrong reasons) or that creativity and humour may overpower the main message ( Algie and Mead, 2019 ). Instead of wearing the risk associated with humorous or experimental content, health authorities may benefit from other social marketing techniques such as sharing popular user generated content or influencer content that aligns with their aims and values ( Hilliard et al , 2021 ; Volkmer, 2021 ). For example, preliminary research into the role of TikTok influencers and COVID-19-related content found that the most popular US TikTok influencers created content that usually demonstrated adherence to public health guidance at the time ( Selkie et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…going viral for the wrong reasons) or that creativity and humour may overpower the main message ( Algie and Mead, 2019 ). Instead of wearing the risk associated with humorous or experimental content, health authorities may benefit from other social marketing techniques such as sharing popular user generated content or influencer content that aligns with their aims and values ( Hilliard et al , 2021 ; Volkmer, 2021 ). For example, preliminary research into the role of TikTok influencers and COVID-19-related content found that the most popular US TikTok influencers created content that usually demonstrated adherence to public health guidance at the time ( Selkie et al , 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has highlighted the importance of communicating reliable health messages to the community during public health emergencies ( Lazarus et al , 2022 ). Given its accessibility and time-sensitivity potential, social media technologies are playing an increasingly significant role in the health communication of governments and public health authorities ( Hilliard et al , 2021 ). During the COVID-19 pandemic, platforms like Facebook, Twitter, Instagram and TikTok emerged as major sources of health information for the public ( Chesser et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%